2019
DOI: 10.1145/3359234
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Skill Provision in Gig Economy from A Network Perspective

Abstract: The recent emergence of gig economy facilitates the exchange of skilled labor by allowing workers to showcase and sell their skills to a global market. Despite the recent effort on thoroughly examining who workers in gig economy are and what their experience in gig economy are like, our knowledge on how exactly workers provide their skills in gig economy, and how worker's strategies of providing and expanding skills relate to their success in gig economy is still lacking. In this paper, we conduct a case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…While skill development in the gig economy remains relatively understudied, skills are still seen as an important aspect of this new form of work (see Ashford et al. (2018) and Huang et al. (2019)).…”
Section: Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…While skill development in the gig economy remains relatively understudied, skills are still seen as an important aspect of this new form of work (see Ashford et al. (2018) and Huang et al. (2019)).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Although skill development may not be among their stated goals, gig economy platforms and applications that digitally connect workers with customers through short-term employment contracts may also allow their users to develop important skills. While skill development in the gig economy remains relatively understudied, skills are still seen as an important aspect of this new form of work (see Ashford et al (2018) and Huang et al (2019)). In the same way that a student can take an online programming class to increase their chances of finding a coding job, gig workers can seek out "gigs" that will help them develop skills for new employment opportunities in the future.…”
Section: Human Capitalmentioning
confidence: 99%
“…On Upwork, the platform uses a ranking tool called the JSS which affects gig worker's ability to bid for jobs; Kinder et al (2019) found that it is difficult for newcomers to get a high JSS until they complete some contracts that result in good reviews. Similarly, Fiverr assigns a "level" to workers based on their activity, performance, and reputation, and workers with higher levels obtain certain benefits when bidding for jobs (Huang et al, 2019). Therefore, there is an entry barrier for new workers, which leads many to bid lower for the same jobs at the very beginning of their employment than will more established workers (Lukac & Grow, 2021).…”
Section: Performance Managementmentioning
confidence: 99%
“…Participants associated entrepreneurial development with keeping domain specific skills updated, but most importantly, learning the essentials of freelance practice (e.g., dealing with clients, managing different projects, and sensemaking of feedback). Huang et al [42] suggest that platforms are in a strong position to encourage freelancers to develop relevant skills. Our findings confirm and expand this notion by showing that platforms can further promote the development of entrepreneurial skills.…”
Section: Supporting the Development Of Entrepreneurial Skillsmentioning
confidence: 99%